anonymous
  • anonymous
Need help for test tomorrow solve please Solve the system by substitution or elimination. Write the answer from the smallest x value to the largest. ie (-2, 5) (3, -4) (7, 2) -x - y + 3 = 0 x2 - 4x + 7 = y
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
steve816
  • steve816
I'll give you help! Why don't you go to sleep so you can focus during the test :)
anonymous
  • anonymous
Thank you
steve816
  • steve816
No problem!

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Can you also answer this Solve the system by substitution or elimination. Write the answer from the smallest x value to the largest. ie (-2, 5) (3, -4) (7, 2) x - 2y = 0 3x - y2 = 0
LynFran
  • LynFran
multiply eq1 by -3 we get -3x+6y=0 3x-y^2=0 add the 2 equations 6y-y^2=0 y(6-y)=0 y=0 and y=6 sub y=0 and or y=6 in eq1 x-2y=0 x-2(6)=0 x=12 when x=12 y=6 (12, 6) x-2(0)=0 x=0 when x=0 y=0 (0,0)
anonymous
  • anonymous
Thank you can you also solve the first equation
LynFran
  • LynFran
ok
steve816
  • steve816
Wow, great explanation @LynFran You are really great with math :)
LynFran
  • LynFran
-x-y+3=0 x^2-4x+7=y rewrite eq1 to -x+3=y now equate the 2 equations we get x^2-4x+7=-x+3 x^2-4x+x=3-7 x^2-3x=-4 (x- 1.5)^2=-4+2.25 (x-1.5)^2=-1.75 ....................please check ur equation to make sure its correctly type..im getting nowhere with this..
anonymous
  • anonymous
-x - y + 3 = 0 x2 - 4x + 7 = y This is it
anonymous
  • anonymous
Can u help me on this You are upset with your satellite TV provider and choose to build your own parabolic satellite dish. You want the dish to be 12 inches across. You want the maximum height of the dish to be 7 feet. What is the value of "a" in the parabolic equation for the dish?

Looking for something else?

Not the answer you are looking for? Search for more explanations.